"Sport saved my life" but "I am tired of being an alien!": Stories from the life of a deaf athlete. (July 2018) - Irish, Thomas; Cavallerio, Francesca; McDonald, Katrina
Abstract: Objectives: This study explores the ways in which a deaf athlete's experiences of participation in sport can affect his psychological and social well-being, and how social and interpersonal relationships play a role in shaping these experiences. Design: To produce an understanding of the embodied experience of being a deaf athlete over the years and in different social situations, an autoethnographic approach was adopted. Method: To generate the stories represented in this study, three main strategies have been adopted: memory writing, emotional recall, and the use of memory. Adopting the position of the storyteller, data was represented through an evocative autoethnography, with the aim to describe subjective emotional experiences to create empathy with, as well as increase awareness and encourage reflection in the reader. Results: Five story fragments taken from a deaf athlete's life are presented, in relation to key moments of the athlete's life. The stories show how social relationships affect the athlete's experience of sport participation, spanning from an enthusiastic inclusion in playing sport with hearing and non-hearing peers, to the feelings of alienation felt due to social exclusion from hearing sport events, and the hopelessness deriving from a lack of understanding of the specific needs that come from coaching a deaf person. Conclusions: The theoretical and practical implications of this study are discussed, with particular attention towards the opportunity of portraying the experiences of a category of athletes that has been scarcely investigated, and even more rarely allowed its own voice. Highlights: Research looking into the experience of deaf people in sport is scarce. Sport can be a positive experience for deaf people but it can also marginalise them. Stakeholders in sport (e.g., coaches) need to be aware of how to effectively work with different types of impairments. Autoethnography can have a therapeutic role for the author and raise awareness and encourage social change in the readers.